2016
DOI: 10.1051/0004-6361/201628769
|View full text |Cite
|
Sign up to set email alerts
|

O VI 1032 Å intensity and Doppler shift oscillations above a coronal hole: Magnetosonic waves or quasi-periodic upflows?

Abstract: On 1996 December 19, the Ultraviolet Coronagraph Spectrometer (UVCS) on board the Solar and Heliospheric Observatory (SOHO) conducted a special high-cadence sit-and-stare observation in the O vi 1032 Å spectral line above a polar coronal hole at a heliocentric distance of 1.38 R . The ∼9-h dataset was analyzed by applying advanced spectral techniques to investigate the possible presence of propagating waves. Highly significant oscillations in O vi intensity (P = 19.5 min) and Doppler shift (P = 7.2 min) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…At heights 1.4 R ⊙ , there have been studies using the Ultraviolet Coronagraph Spectrometer (UVCS) on the Solar and Heliospheric Observatory (SOHO). Using an O vi line at 1.4 R ⊙ , Mancuso et al (2016) found intensity oscillations with periods of ∼ 20 minutes and amplitudes of ∆I/I ≈ 10% (∆n e /n e ≈ 5%). It is interesting that these large amplitudes, similar to those found near the limb, were found at such large heights as dissipation is expected to reduce acoustic wave amplitudes as the waves propagate (Ofman et al 1999(Ofman et al , 2000.…”
Section: Introductionmentioning
confidence: 98%
“…At heights 1.4 R ⊙ , there have been studies using the Ultraviolet Coronagraph Spectrometer (UVCS) on the Solar and Heliospheric Observatory (SOHO). Using an O vi line at 1.4 R ⊙ , Mancuso et al (2016) found intensity oscillations with periods of ∼ 20 minutes and amplitudes of ∆I/I ≈ 10% (∆n e /n e ≈ 5%). It is interesting that these large amplitudes, similar to those found near the limb, were found at such large heights as dissipation is expected to reduce acoustic wave amplitudes as the waves propagate (Ofman et al 1999(Ofman et al , 2000.…”
Section: Introductionmentioning
confidence: 98%
“…Over the last few decades, a technique called singular spectral analysis (SSA;Vautard & Ghil 1989) and its multivariate extension (MSSA; Ghil et al 2002) have been widely used in the identification of oscillations in climatic time series (e.g., Taricco et al 2015ab). Recently, this technique has been successfully applied in the analysis of Doppler shift oscillations in the UV corona (Mancuso et al 2015(Mancuso et al , 2016. One of the main advantages of MSSA with respect to classical Fourier methods is its ability to detect common non-sinusoidal oscillations that are modulated both in amplitude and phase so that the original signals are no more simply decomposed into periodic sinusoidal functions but into data-adaptive waves.…”
Section: Analysis and Preliminary Resultsmentioning
confidence: 99%
“…The original time-evolving signal is not simply decomposed into periodic sinusoidal functions as in Fourier-like techniques, but broken down into data-adaptive waves that can be modulated both in amplitude and phase. Although not commonly used in astrophysical contexts, this powerful technique has recently been applied to successfully detect Doppler-shift oscillations in the UV corona (Mancuso & Raymond 2015;Mancuso et al 2016), analyze quasi-biennial oscillations of the Fe xiv green coronal emission line at 5303 Å (Mancuso et al 2018), and, more recently, to detect multiple quasi-periodic pulsations observed during the flaring activity of a young, active solar-type star observed by the Kepler mission (Mancuso et al 2020). Its multivariate extension, the so-called multichannel singular spectrum analysis (MSSA), has the additional ability to identify coherent space-time patterns and thus extract common periodic signals, trends and noise from a multivariate dataset (e.g., Taricco et al 2015;Mancuso et al 2018).…”
Section: Multichannel Singular Spectrum Analysismentioning
confidence: 99%